Application analysis tools for ASIP design application profiling and instruction-set customization - Karuri, Kingshuk (Springer, 2011)
This book provides an overview of the recent advancements in cutting edge design automation tools for Application Specific Instruction-set Processor (ASIP) development. ASIPs are becoming increasingly common in many embedded System-on-Chip architectures due to their unique blend of flexibility and performance/energy efficiency. However, the high development effort associated with ASIPs has so far hindered their widespread acceptance in the embedded world. This book introduces readers to a novel design methodology which can significantly reduce the ASIP development effort through high degrees of design automation. The key elements of this new design methodology are a powerful application profiler and an automated instruction-set customization tool which considerably lightens the burden of mapping a target embedded application to an ASIP architecture in the initial design stages. The book includes several design case studies with realistic embedded applications to demonstrate how the methodology and the tools can be used in practice to accelerate the overall ASIP design process. ? Provides a thorough survey of ASIP design in general, and application analysis (profiling and instruction-set customization) in particular; Introduces several original concepts/tools, as well as algorithms and software architectures, to enable readers to build similar ASIP development tool flows from scratch;? Includes case studies that systematically demonstrate how ASIPs can be built using application analysis tools presented in the book.